Set the Technical Information Secret in the Possession of the Contractor (مجلة المنصور, 2022)
The technical information is characterized with the Clandestineness ingeneral , that’s because it always regarded as an object of the contractconcluded between the the supplier and the beneficiary, that secretinformation if it declared it will be loses their Physical value, theconsequence of the relationship of these parties arranging some influencea cause of the contract and what accompanied with stages the technologytransfer contract’s are not from the concept and nature other contracts it’sdeferent form of trading contract, the object in these contract is technicalevent represente with trance technical knowledge on the other hand ithas characterizing properties unique from other , international character ispredominant them, as well as the obligations are deferent in such kind of contract which is lies on each party . Finally I tried to determined the Intended of the right’s possession for the technical information , how it achieved ?, what it’s purpose of ? trying todistinguished between the legal possession and the physical possession , without fail to mention the impact of each on , in the same context how the stable possession can be achieved .